PERLINDUNGAN HUKUM BAGI HAK-HAK NARAPIDANA DALAM KASUS PERCERAIAN DI PENGADILAN AGAMA - Kurniawati, Wa Ode Intan; Saprudin, Saprudin; Ismail, La Ode; Muhram, La Ode; Yulian Yusuf, Niken; Suprayogi Yusuf, Virya; Hayati, Sri; Rosta, Moses; Apriani, Leny (JICS : Journal Of International Community Service, 2024)
This study aims to analyze the legal protection of the rights of prisoners in the divorce process that takes place in the Religious Court. The method used in this research is a qualitative approach using case studies and in-depth interviews with several prisoners who are undergoing divorce at the Religious Court, as well as judges and related legal practitioners. The results show that although prisoners have the right to apply for divorce and receive legal protection, there are a number of challenges faced, including limited access to attend the trial in person, as well as communication problems between prisoners and legal counsel. Religious Courts tend to accommodate divorce proceedings through remote court facilities, but not all prisoners have sufficient understanding of the procedure. The contribution of this research is to provide recommendations for improving the legal system in the Religious Courts to provide maximum protection for prisoners in divorce cases